Hubungan Tingkat Pengetahuan Dengan Keikutsertaan Keluarga Berencana Pada Pria - Deka Ramita; Setyowati; Niken Meilani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2023)
Background: Uncontrolled population growth leads to various issues, including social, economic, political, and security concerns. The solution to address this is through a family planning program. However, family planning programs are predominantly focused on women. Male participation in family planning is still very low, as indicated by the low coverage of male contraceptive use. Limited knowledge among men about family planning is one of the causes of low male participation in family planning. Purpose: To determine the relationship between knowledge level and family planning participation in men in the working area of Koba Central Health Center. Method: The research is a quantitative study with a case-control design. The population consists of all fertile-age male couples (reproductive age group) in the UPTD Koba Health Center area, Bangka Regency. The sample consists of 53 respondents for both the case and control groups, selected through accidental sampling. The case group comprises reproductive age group participants in family planning. The control group consists of reproductive age group individuals who are not family planning participants. Data collection was done using a questionnaire. Data analysis techniques used chi-square. Results: The knowledge level of family planning in the case group mostly falls under the good category (71.7%), while in the control group, it mostly falls under the poor category (50.9%). Male participation in family planning mostly involves condom use (92.5%), has been using contraception for ≤ 5 years (58.5%), and regular condom users (87.8%). There is a relationship between knowledge level of family planning and male participation in family planning, with a chi-square value of 4.772 and p-value of 0.029 (p < 0.05). Men with good knowledge of family planning are 2.631 times more likely to be family planning acceptors compared to men with poor knowledge of family planning. Conclusion: There is a relationship between knowledge level of family planning and male participation in family planning. Keywords: Knowledge, Family planning participation, Men.